2014
DOI: 10.1186/1471-2164-15-916
|View full text |Cite
|
Sign up to set email alerts
|

Changes in renal medulla gene expression in a pre-clinical model of post cardiopulmonary bypass acute kidney injury

Abstract: BackgroundAcute kidney injury (AKI) is a common and serious complication of cardiac surgery using cardiopulmonary bypass (CPB). The pathogenesis is poorly understood and the study of AKI in rodent models has not led to improvements in clinical outcomes. We sought to determine the changes in renal medullary gene expression in a novel and clinically relevant porcine model of CPB-induced AKI.ResultsAdult pigs (n = 12 per group) were randomised to undergo sham procedure, or 2.5 hours CPB. AKI was determined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
1
14
1
Order By: Relevance
“…Porcine models of CPB‐induced AKI are preferred for translational research because of their significant homology to AKI in cardiosurgical patients . Several studies have demonstrated via biochemical and histological measures that porcine models have a higher degree of functional, urinary and histological similarities to humans than do rodent models …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Porcine models of CPB‐induced AKI are preferred for translational research because of their significant homology to AKI in cardiosurgical patients . Several studies have demonstrated via biochemical and histological measures that porcine models have a higher degree of functional, urinary and histological similarities to humans than do rodent models …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Hb levels were higher in the HTK‐N group than in the HTK group. We hypothesized that the addition of the iron chelators deferoxamine and LK‐614 to the HTK‐N solution could be responsible for the reduction of CPB‐induced hemolysis that is associated with the production of free Hb and free iron …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to use a porcine model due to the similarities in both the physiologic response to CPB and drug metabolism. [87][88][89][90][91][92] However, staged clinical trials in children and adults undergoing cardiac surgery are needed to de nitively prove both the safety and e cacy of this therapy. While it is possible to differentiate among human AP isoenzymes/isoforms, [46] the previously published lack of available antibodies to exogenous BiAP and native non-human AP makes this differentiation challenging in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…The latter can provide a more suitable setting to simulate surgical practices and/or replicate scenarios, e.g. large animal models in AKI research (Ghorbel et al, 2014), instead of murine models that are unlikely to mimic sufficiently the pathology of the surgical scenarios of interest ).…”
Section: Translational Outlook and Conclusionmentioning
confidence: 99%